Perceptions and strategies of healthcare professionals regarding cultural beliefs and practices in the management of paediatric chronic diseases in Kinshasa - DIWOTO DOWO, Jean-Paul; Amuli , Jiwe Jean-Pierre; Mabakutuvangilanga, Ntela Simon-Decap; Mukandu, Basua Babintu Leyka (Orapuh Journal, 2025)
Introduction In Kinshasa, the management of paediatric chronic diseases occurs within a context of strong cultural diversity. Traditional beliefs and practices influence healthcare decisions and present complex challenges for health professionals. This study explores their perceptions and the strategies developed to address these cultural realities. Purpose To understand healthcare professionals’ perceptions of the impact of cultural beliefs and to identify the strategies implemented in managing paediatric chronic diseases. Methods A qualitative exploratory study was conducted at the Renaissance University Hospital Centre. Ten nurses participated in semi-structured interviews. None of them had received specialised training in intercultural communication. Data were analysed using Braun and Clarke’s thematic approach, with reference to Leininger’s transcultural theory. Results Three main challenges were identified: (1) persistent cultural misunderstandings, (2) partial or complete rejection of biomedical treatments, and (3) lack of training in cultural competence. The strategies adopted included partial adaptation of care, intercultural dialogue, and controlled tolerance of certain non-invasive family practices. Conclusions This is the first study in Kinshasa addressing healthcare professionals’ strategies in relation to cultural beliefs. The findings highlight the need to strengthen cultural competence among healthcare staff. Institutionalising cultural mediator roles and integrating intercultural communication modules into continuing education should be prioritised to improve both care quality and the caregiver–patient relationship.